Sinergi Mahasiswa dan Masyarakat: Implementasi Program PKLPP UMS di Ngemplak, Kartasura: Student and Community Synergy: Implementation of the UMS PKLPP Program in Ngemplak, Kartasura - Alina Naura Ayu; Voni Nilla Agustin; Ashly Indah Fitriyani; Briliana Fian Hartanti; Ahmad Nurrohim (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Ngemplak Village, Kartasura has agricultural potential, craft UMKM, and dynamic religious life, but the learning process in the Al-Qur'an Education Park (TPA) is still monotonous, learning media is limited, and attention to the health of residents is not optimal. The Field Work Practice Program for Community Service and Empowerment (PKLPP) of Muhammadiyah University of Surakarta was designed to answer these problems with a six-week participatory action approach. The stages of the activity include regional portraits and needs analysis, program planning with partners, preparation of modules and measuring instruments, and tiered implementation—Qur'an reading assistance, creative literacy workshops for lapbooks, calligraphy coloring competitions, to social health services and distribution of basic necessities. As a result, the participation of TPA students increased by ±40%, 30 lapbooks were created as permanent learning media in the mosque library, and 42 children were involved in a calligraphy competition that increased appreciation of Islamic art. In addition, 40 residents received free health checks, while 50 packages of basic necessities and organic vegetables were distributed to underprivileged families. Interviews with community leaders showed growing trust in students as facilitators and the emergence of sustainable ideas in the form of digital Quran classes, family literacy clinics, and healthy snack UMKM training. These findings confirm that student-community synergy can strengthen Quranic literacy capacity, children's creativity, and social-health concerns in a sustainable manner.